A Ge.F.I. – ISFG European collaborative study on DNA identification of Cannabis sativa samples using a 13-locus multiplex STR method. (December 2021) - Di Nunzio, M.; Agostini, V.; Alessandrini, F.; Barrot-Feixat, C.; Berti, A.; Bini, C.; Bottinelli, M.; Carnevali, E.; Corradini, B.; Fabbri, M.; Fattorini, P.; Garofano, P.; et al.
Abstract: Cannabis sativa is the most used controlled substance in Europe. With the advent of new and less restrictive European laws on cannabis sale for recreational use (including in Italy), an increase in indoor cannabis crops were observed. This increase was possible due to the availability of cannabis seeds through the internet market. Genetic identification of cannabis can link seizures and if in possession then might aid in an investigation. A 13-locus multiplex STR method was previously developed and validated by Houston et al. A collaborative exercise was organized by the Italian Forensic Geneticists – International Society of Forensic Genetics (Ge.F.I. – ISFG) Working Group with the aim to test the reproducibility, reliability and robustness of this multiplex cannabis STR kit. Twenty-one laboratories from three European countries participated in the collaborative exercise and were asked to perform STR typing of two cannabis samples. Cannabis DNA samples and the multiplex STR kit were provided by the University of Barcelona and Sam Houston State University. Different platforms for PCR amplification, capillary electrophoresis (CE) and genotyping software were selected at the discretion of the participating laboratories. Although the participating laboratories used different PCR equipment, CE platforms and genotyping software, concordant results were obtained from the majority of the samples. The overall genotyping success ratio was 96%. Only minor artifacts were observed. The mean peak height ratio was estimated to be 76.3% and 78.1% for sample 1 and sample 2, respectively. The lowest amount of −1 / + 1 stutter percentage produced, when the height of the parent allele was higher than 8000 RFU, resulted to be less than 10% of the parent allele height. Few common issues were observed such as a minor peak imbalance in some heterozygous loci, some artifact peaks and few instances of allelic drop-out. The results of this collaborative exercise demonstrated the robustness and applicability of the 13-locus system for cannabis DNA profiling for forensic purposes. Highlights: A collaborative exercise was carried out between 2020 and 2021 within ISFG-Ge.F.I. The exercise was focused on a 13-locus multiplex Cannabis sativa STR kit. The outcome was that typing success percentage varied from 69.2% to 100%. Some training on this new Forensic Plant STRs will be necessary.